Про взаємозв’язок часових змін магнітного поля Землі з сонячною активністю 19—24-го циклів - Орлюк, М.І.; Роменець, А.А. (Доповіді НАН України, 2022)
Досліджено часові зміни головного геомагнітного поля BIGRF на поверхні Землі співвідносно із сонячною активністю для 19—24-го циклів. Встановлено, що зменшення поля ВIGRF на поверхні планети на 1800 нТл добре узгоджується зі зменшенням сонячної активності починаючи з 19-го циклу і дотепер. Іншою важливою виявленою закономірністю є певна узгодженість кривих тренду сонячної активності і відповідної кривої часового градієнта геомагнітного поля (вікової зміни). Показано досить чіткий зв’язок часового градієнта геомагнітного поля (вікових варіацій) з 11- та 22-річними (Хейла) циклами сонячної активності. Зміна геомагнітного поля з періодом циклу Хейла (20—22 р.) добре узгоджується з характером великомасштабного поля Сонця. Особливо важливим результатом є встановлений зв’язок із сонячною активністю не тільки варіацій та збурень геомагнітного поля зовнішнього походження, але і змін та варіацій головного магнітного поля Землі BIGRF, механізм генерації якого зв’язаний з її ядром. The article presents the results of studies concerning the temporal changes of the main geomagnetic field BIGRF on the Earth’s surface with solar activity for 19-24 cycles. According to the results of the study, it was found that a decrease in the BIGRF field on the planet’s surface by 1800 nT corresponds to a decrease in solar activity, starting from cycle 19 to the present. Another important revealed regularity is a certain interdependence of the solar activity trend curves and the corresponding curve of the temporal gradient of the geomagnetic field (secular variation). A fairly clear connection between the temporal gradient of the geomagnetic field (secular variations) and 11-year and 22-year (Hale) cycles of solar activity is shown. Therefore, the change in the geomagnetic field with the period of the Hale cycle (20-22 years) is in good agreement with the nature of the large-scale field of the Sun. A particularly important result is the established connection with solar activity not only of variations and disturbances of the geomagnetic field of external nature, but also of changes and variations of the main magnetic field of the Earth BIGRF, the generation mechanism of which is associated with its core.